1996
DOI: 10.1111/j.1399-6576.1996.tb04562.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of tracheal and intravenous adrenaline in infants with congenital heart anomalies

Abstract: Tracheal administration 3 micrograms/kg adrenaline increased mean arterial blood pressure in infants with congenital cardiac anomalies, but the increase occurred later and was less consistent than after 0.3 microgram/kg of adrenaline given intravenously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although early experimental work by Redding et al 17 suggested that a ETT epinephrine dose (0.1 mg/kg) would be as effective as intravenous epinephrine in achieving return of spontaneous circulation from asphyxia-induced cardiac arrest, most subsequent studies demonstrated that ETT epinephrine is poorly or slowly absorbed and takes longer to work. [9][10][11][12] Many investigators report that even in adult animal models 10,12,[18][19][20] and human patients with intact circulation [21][22][23] (and thus likely sufficient pulmonary perfusion), Ն10 times the currently recommended dose of ETT epinephrine is required to achieve equivalent increases in plasma epinephrine concentrations or to elicit any physiologic effect, such as a rise in blood pressure, when compared with intravenous epinephrine. Manisterski et al 24 compared different doses of ETT epinephrine, ranging from 0.02 to 0.3 mg/kg, in healthy anesthetized dogs, but only 10 to 30 times the currently recommended dose (0.3 mg/kg) led to a sustained increase in blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Although early experimental work by Redding et al 17 suggested that a ETT epinephrine dose (0.1 mg/kg) would be as effective as intravenous epinephrine in achieving return of spontaneous circulation from asphyxia-induced cardiac arrest, most subsequent studies demonstrated that ETT epinephrine is poorly or slowly absorbed and takes longer to work. [9][10][11][12] Many investigators report that even in adult animal models 10,12,[18][19][20] and human patients with intact circulation [21][22][23] (and thus likely sufficient pulmonary perfusion), Ն10 times the currently recommended dose of ETT epinephrine is required to achieve equivalent increases in plasma epinephrine concentrations or to elicit any physiologic effect, such as a rise in blood pressure, when compared with intravenous epinephrine. Manisterski et al 24 compared different doses of ETT epinephrine, ranging from 0.02 to 0.3 mg/kg, in healthy anesthetized dogs, but only 10 to 30 times the currently recommended dose (0.3 mg/kg) led to a sustained increase in blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…There are concerns that the endotracheal route may not result in as eective a level of epinephrine as does the intravenous route [41,47,49,53]; however, the data are insucient to recommend a higher dose via the endotracheal route. There are concerns that the endotracheal route may not result in as eective a level of epinephrine as does the intravenous route [41,47,49,53]; however, the data are insucient to recommend a higher dose via the endotracheal route.…”
Section: Routes Of Medication Administrationmentioning
confidence: 99%